English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2. -(2x - 6)=X

-3
-1
3
-2
2

2007-01-07 08:52:13 · 12 answers · asked by shariff B 1 in Science & Mathematics Mathematics

12 answers

1. 6x + (2x + 6) = x + 27
(add like terms)
8x + 6 = x + 27
(subtract x from each side and subtract 6 from each side)
7x = 21
(divide each side by 7)
x = 3 <--- Final answer.

2. -(2x - 6) = x
(distribute negative 1)
-2x + 6 = x
(add 2x to both sides)
6 = 3x
(divide each side by 3)
2 = x <--- Final answer.

2007-01-07 09:04:33 · answer #1 · answered by ♥ Dani 6 · 1 0

The only difference in this problem is that it has ( ) All you have to know about ( ) is that you take the sign--in this case + and multiply each number in the ( ), then you have a problem without ( ), which is solved in the same manner as the one covered below. PLEASE TRY and work the problem yourself. (I know a few people already gave you the answer, but you really need to understand the how and the why.)

Why do you keep asking the same question over and over? Granted the numbers are different, but don't you realize that the manner in which you solve this problems is all the same? You are seriously being lazy or maybe you just don't understand "AT ALL" and think that this is helping you. IT ISN'T. Algebra is EASY---this junk is. What you need to do to ALL of these problems is put together your like terms?

8z + 5 - 10z = -3

Its like terms are: 1. All your numbers with a z and 2. All your numbers that don't have a z. Decide which side you want each on on. Most times just leave the letters to the left and send the numbers without letters to the right.

8z + 5 - 10z = -3
Now get rid of the 5, since it is +5 you can conclude that it is a positive number. What is the opposite of positive? Why it is negative so subtract the 5 from the left and then you move it to the right. You subtract it from -3 on the right.

8z-10z = -3-5

Now just add or subtract your zs on the left and your numbers on the right.
-?z = -?

I'm not giving you the next step--I mean can't you subtract and add? The only thing I am goinf to say is as far as the left side is concerned with the zs, when you have a + sign and a - sign you subtract and take the sign from the larger number (Being bigger makes it is his victory right?)
On the right side, if you have the same + or - sign simply add and accept the sign they both already have.

You should have this:

-?numberz = -?number

Now divide the -?number from the z and then send it to the right and divide it as well.

You should have
z= +?number (What happened here, why is it +, well, when you divide a - by a - you get a +, don't worry about why, just accept it and memorize that fact. A negative divided by a negative is a positive---same goes for multiplication a negative times a negative is a positive.

In order to check your answer just plug the number you got as your value for z and work out the problem. If it is a true statement then it is right, if not just try again. Don't get discouraged. And please, don't make another post asking for the answer to the same type of problem. Use your brain and you'll be better off in the long run,...after all, we can't be there to help you on test day, can we?

2007-01-07 19:10:04 · answer #2 · answered by BookLady 3 · 0 0

3

2007-01-07 16:55:11 · answer #3 · answered by Evermore 3 · 1 0

1. *Eliminate parenthesis > rewrite the equation without parenthesis > combine "like" terms >

6x + 2x + 6 = x + 27
8x + 6 = x + 27

First: subtract "x" from both sides >

8x - x + 6 = x - x + 27
7x + 6 = 27

Sec: subtract 6 from both sides >

7x + 6 - 6 = 27 - 6
7x = 21

Third: solve for "x" by isolating it on one side >divide both sides by 7 >

7x/7 = 21/7
x = 3

2. -(2x - 6) = x
First: distribute the negative sign with terms in the parenthesis > add 2x to both sides >

-2x + 6 = x
-2x + 2x + 6 = x + 2x
6 = 3x

Sec: divide both sides by 3 >

6/3 = 3x/3
2 = x; x = 2

2007-01-07 17:07:13 · answer #4 · answered by ♪♥Annie♥♪ 6 · 1 0

x = 3 because:
6x + 2x + 6 = x + 27 (the parentheses doesn't make a difference here)
makes it equal to 8x + 6 = x + 27.

then you move the x over and the 6 over, so it will be:
7x = 27-6
7x = 21
divide by 7 to both sides
x = 3.

2007-01-07 17:03:07 · answer #5 · answered by Soybean 1 · 1 0

6x +(2x+ 6) =x + 27
6x+2x-x=27-6
7x=21
x=3

-(2x - 6)=X
-2x+6=x
-2x-x=-6
-3x=-6
x=2

2007-01-07 18:05:50 · answer #6 · answered by Saphira 3 · 0 0

6x +(2x+ 6) =x + 27
8x +6=x+27
7x+6=27
7x=21
x=3

-(2x - 6)=X
-2x+6=x
-3x=-6
X=2

2007-01-07 17:06:11 · answer #7 · answered by Anonymous · 1 0

3....
sub. the x from the right side on both sides...
addition can be done in any order...add the 5x(from sub. the x from bothsides) left with 7x+6=27
subtract 6 from both sides 7x=21....divide by 7

2007-01-07 17:03:37 · answer #8 · answered by stupidsquarejew08 1 · 1 0

The 1st one is 3, Evermore got it right. The 2nd one is 2.

2007-01-07 17:03:59 · answer #9 · answered by mitcardinal 1 · 1 0

-3

2007-01-07 16:59:15 · answer #10 · answered by Anonymous · 0 2

fedest.com, questions and answers